The Clock-in-the-Box, a brief cognitive screen, is associated with failure to return home in an elderly hospitalized sample - Jackson CE (Dove Medical Press, 2016)
Colleen E Jackson,1–3 Laura J Grande,1–3 Kelly Doherty,1 Elizabeth Archambault,1 Brittany Kelly,1 Jane A Driver,1,4 William P Milberg,1,2,5 Regina McGlinchey,1,2,5 James L Rudolph6,7 1Geriatric Research, Education and Clinical Center, Department of Veterans Affairs (VA) Boston Healthcare System, Boston, MA, 2Translational Research Center for TBI and Stress Disorders, Department of Veterans Affairs (VA) Boston Healthcare System, Boston, MA, 3Department of Psychiatry, Boston University School of Medicine, Boston, MA, 4Department of Medicine, Harvard Medical School, Boston, MA, 5Department of Psychiatry, Harvard Medical School, Boston, MA, 6Center of Innovation in Long Term Services and Supports, Department of Veterans Affairs (VA) Providence Medical Center, Providence, RI, 7Department of Medicine, Warren Alpert School of Medicine of Brown University, Providence, RI, USA Purpose: Cognitive screening upon hospital admission can provide important information about the patient’s ability to process information during the inpatient stay. The Clock-in-the-Box (CIB) is a rapidly administered cognitive screening measure which has been previously validated with cognitive screening and neuropsychological assessments. The purpose of this study is to demonstrate the predictive validity of the CIB for discharge location among a sample of older medical inpatients. Patients and methods: Hospitalized Veterans (N=218), aged 55 years and older, were recruited on the day after admission after they gave their consent. These participants completed the CIB, the Montreal Cognitive Assessment, and self-report measures of daily functioning. Using logistic regression models, the bivariable and multivariable impact of the cognitive screening and functional assessments were examined for their ability to predict whether the participants did not return home after hospitalization (eg, admission to subacute rehabilitation facilities or nursing facilities). Results: The participants were older (mean 71.5±9.5 years) and predominantly male (92.7%). The CIB score was independently associated with discharge to locations other than home (odds ratio =0.72, 95% confidence interval =0.60–0.87, P=0.001) and remained associated after adjusting for demographics, prehospitalization functional abilities, and Montreal Cognitive Assessment score (adjusted odds ratio =0.55, 95% confidence interval =0.36–0.83, P=0.004). Conclusion: The current evidence, combined with its brevity and ease of use, supports the use of the CIB as a cognitive screen for inpatient older adults, in order to help inform clinical treatment decisions and discharge planning. Keywords: cognition, screening, aging, hospitalization, care transition